The Effectiveness of Giving Cognitive Behavior Therapy (CBT) and Mindfulness Therapy on Adolescents' Social Anxiety Levels - Yulia Sukmawati; Retno Lestari; Viera Wardhani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Social anxiety is a serious problem occurring in early adolescence characterized by a high level of worry, negative evaluation, and avoidance behavior in various social situations. The existence of fear, worry, and unconsciousness in recognizing negative thoughts that cause avoidance in adolescents with social anxiety problems can be overcome by providing CBT and Mindfulness therapy. This study aims to identify the effectiveness of Cognitive Behavior Therapy (CBT) and mindfulness therapy on adolescent social anxiety problems. this research is a research quasi-experimental pre-test post-test control group design. There were 40 participants in this study, namely 20 students in the control group and 20 students in the treatment group. The results obtained from this study were that there were differences in the effectiveness of giving CBT with a combination of CBT and mindfulness in adolescent social anxiety with a p-value of 0.002 (0.002 less than 0.05) which was marked by a decrease in the average score of social anxiety in the group given the CBT combination intervention and mindfulness were greater compared to adolescents who were only given CBT. So it can be concluded that the effectiveness of giving a combination of CBT and mindfulness is better than giving CBT to adolescents who experience social anxiety problems. Abstrak: Kecemasan sosial merupakan masalah serius terjadi pada usia remaja awal ditandai dengan tingkat kekhawatiran tinggi evaluasi negatif dan perilaku penghindaran dalam berbagai situasi sosial. Adanya ketakutan, kekhawatiran serta ketidak sadaran dalam mengenali pikiran negatif yang menyebabkan penghindaran pada remaja dengan masalah kecemasan sosial dapat diatasi dengan pemberian terapi CBT dan Mindfulness. Penelitian ini bertujuan untuk mengidentifikasi efektifitas pemberian Cognitive Behaviour Therapy (CBT) dan terapi mindfullness pada masalah kecemasan sosial remaja. Penelitian ini adalah penelitian quasi eksperimental pre-test post-test control group design. Terdapat 40 peserta dalam penelitian ini yaitu 20 siswa dalam kelompok kontrol dan 20 siswa dalam kelompok perlakuan. Hasil yang didapatkan dari penelitian ini adalah bahwa ada perbedaan efektifitas pemberian CBT dengan kombinasi CBT dan mindfulness terhadap kecemasan sosial remaja dengan nilai p-value 0.002 (0.002 kurang dari 0.05) yang ditandai dengan penurunan skor rata-rata kecemasan sosial pada kelompok yang diberikan intervensi kombinasi CBT dan mindfulness lebih besar dibandingkan dengan remaja yang hanya diberikan CBT saja. Sehingga dapat disimpulkan bahwa efektifitas pemberian kombinasi CBT dan mindfulness lebih baik dibandingkan dengan pemberian CBT pada remaja yang mengalami masalah kecemasan sosial.